Microbiology - Black, Jacquelyn G.; Black, Laura J. (Hoboken, NJ : Wiley, 2013)
"Jacquelyn Black's 8th Edition of Microbiology: Principles and Explorations builds upon the previous best-selling textbooks in this series with an enhanced introduction to the study of Microbiology in the same engaging writing style throughout the narrative. The text's is even more reader-friendly and focuses on microbiology, allied health, agriculture and food sciences topics"--
Machine generated contents note: 1. Scope and History of Microbiology.2. Fundamentals of Chemistry.3. Microscopy and Staining.4. Characteristics of Prokaryotic and Eukaryotic Cells.5. Essential Concepts of Metabolism.6. Growth and Culturing of Bacteria.7. Microbial Genetics.8. Gene Transfer and Genetic Engineering.9. An Introduction to Taxonomy: The Bacteria.10. Viruses.11. Eukaryotic Microorganisms and Parasites.12. Sterilization and Disinfection.13. Antimicrobial Therapy.14. Host-Microbe Relationships and Disease Processes.15. Epidemiology and Nosocomial Infections.16. Innate Host Defenses.17. Basic Principles of Adaptive Immunity and Immunization.18. Immune Disorders.19. Diseases of the Skin and Eyes; Wounds and Bites.20. Urogenital and Sexually Transmitted Diseases.21. Diseases of the Respiratory System.22. Oral and Gastrointestinal Diseases.23. Cardiovascular, Lymphatic, and Systemic Diseases.24. Diseases of the Nervous System.25. Environmental Microbiology.
Includes index.
Keywords: Microbiology